Rate and Indications of Caesarean Section in College of Medical Sciences and Teaching Hospital- A Retrospective Study - Tara Manandhar (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Caesarean Section (CS) is the most common abdominal surgery in obstetrical practice and it is in increasing trend. Aim: To analyse the rate and indication for CS in our institute. Materials and Methods: A retrospective study was conducted in which the medical records of patients who underwent Lower Segment Caesarean Section (LSCS) at our institution from February 2010 to February 2012 were analysed. Various obstetrical parameters including rate and indications of Caesarean section were analysed. Results: Out of 1412 deliveries, 412 patients had CS over the two year study period. The mean (SD; range) age of patients was 24.4 (4.2; 16-42) years, mean (SD; range) period of gestation was 38.6 (2.2; 29.6-43.5) weeks. Primigravida accounted for 54.4% of the patients. Emergency LSCS was done in 79.1%. Previous CS, severe oligohydramnios and foetal malpresentations were the common indications for LSCS accounting to 16.9, 15.8 and 13.6% respectively. The CS rate was 29.17%. There was no maternal mortality. Conclusion: CS is a common and a safe mode of delivery whenever indicated. Unjudicial CS poses threat rather than improving feto-maternal outcome; hence the rate of caesarean should be kept to the minimal recommended threshold level.